The German Act on Corporate Due Diligence Obligations in supply chains: An empirical assessment of the agri-food supply chain based on experts’ perspectives - Abdulaziz Mardenli; Katharina Friederike Sträter; Christoph Herrmann; Dirk Sackmann (Cleaner Logistics and Supply Chain, 2025)
The consideration of social and environmental sustainability (in the following: sustainability) in supply chains (SCs) has gained importance in recent years. Consequently, the view that globally-acting companies should bear responsibility for their entire supply chain has become more and more established. Germany, to codify this responsibility, adopted the Act on Corporate Due Diligence Obligations in Supply Chains (LkSG) in 2021, which came into effect in 2023. The LkSG holds companies accountable for protecting human rights and complying with environmental standards. It requires them to monitor risks along their SCs and to identify and mitigate respective problems. Focusing on the agri-food supply chain, which is frequently the core of discussions regarding a lack of sustainability, and based on 17 semi-structured interviews with experts, this study exemplarily assesses companies’ perceptions of the LkSG’s requirements. It, therefore, aims to bridge the gap between the legal framework and practical implementation, thus, contributing to the understanding of the LkSG’s effectiveness in promoting sustainability. The findings reveal a dichotomous picture: large, established companies are perceived to be less affected due to their existing transparency and compliance infrastructure. On the contrary, smaller and less established companies are expected to face significant challenges, particularly in terms of administrative burden and resource allocation. Although the motivation behind the LkSG is generally seen as well-founded, its complexity and compliance costs are perceived as substantial, highlighting the tension between sustainability and profit, which is also reflected in the interviewees’ importance rating of Key Performance Indicators (KPIs).